Armostrong's Handbook of Strategic Human Resource Management - Armstrong Michael (Kogan Page, 2011)
An indispensable text that includes new material on international aspects of strategic human resource management. Introduction, The Conceptual Framework of Strategic HRM, The Concept of HRM, The Concept of Strategic Human Resource Management, The Practice of Strategic HRM, The Strategic Role of HR, The Impact of Strategic HRM, Strategic HRM in Action, Strategic International HRM, HR Strategies, The Framework of HR Strategy, Business Model Innovation, High Performance Strategy, Human Capital Management Strategy, Corporate Social Responsibility Strategy, Organization Development Strategy, Engagement Strategy, Knowledge Management Strategy, Resourcing Strategy, Talent Management Strategy, Learning and Development Strategy, Reward Strategy, Employee Relations Strategy, The Strategic HRM Toolkit, Author and Subject Index.